2013
DOI: 10.1111/aji.12076
|View full text |Cite
|
Sign up to set email alerts
|

Altered Transcriptional Regulation of Cytokines, Growth Factors, and Apoptotic Proteins in the Endometrium of Infertile Women with Chronic Endometritis

Abstract: The altered gene endometrial expression may explain the impaired endometrial receptivity and the finding of endometrial hyperplastic lesions in women affected by CE.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
89
0
10

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 118 publications
(109 citation statements)
references
References 27 publications
2
89
0
10
Order By: Relevance
“…It is therefore possible to speculate that a chronic inflammatory process in the endometrium could influence JZ functionality. In women with CE, an abnormal pattern of lymphocyte subsets and, consequently, an aberrant endometrial microenvironment have been demonstrated (18,19). It is possible to speculate that the altered leukocyte population and the altered pattern of paracrine factors could influence the nearby endometrium of the JZ, inducing an altered contractility.…”
Section: Discussionmentioning
confidence: 99%
“…It is therefore possible to speculate that a chronic inflammatory process in the endometrium could influence JZ functionality. In women with CE, an abnormal pattern of lymphocyte subsets and, consequently, an aberrant endometrial microenvironment have been demonstrated (18,19). It is possible to speculate that the altered leukocyte population and the altered pattern of paracrine factors could influence the nearby endometrium of the JZ, inducing an altered contractility.…”
Section: Discussionmentioning
confidence: 99%
“…S4C). In addition, IFN-stimulated genes, some cytokines and chemokines in the endometrium related to implantation, including CCL2, CCL4, CCL20, CCL5 , and CXCL8 16171819, were also up-regulated. Another up-regulated gene, CSF1 , is a specific hemopoietic growth factor regulating survival, proliferation and differentiation of mononuclear phagocytes.…”
Section: Resultsmentioning
confidence: 98%
“…Whereas, a lot of IFN-stimulated genes including ISG family, IFIT, IRF, MX , and some cytokines/chemokines including CCL2, CCL4, CCL20, CCL5, and CXCL8 16171819 were up-regulated. Among these genes, OPN was a powerful gene involved in embryo implantation.…”
Section: Discussionmentioning
confidence: 98%
“…In EM with CE, the IGFBP1 gene was upregulated, whereas genes such as IGF1 , IL-11 , and CCL4 were downregulated [66]. IGF1 mediated the effect of estrogen on endometrial proliferation, while IGF2 mediated the effect of progesterone during the secretory phase by facilitating the implantation and invasion of embryos [596768].…”
Section: Pathophysiology Of Cementioning
confidence: 99%
“…In summary, chronic endometrial inflammation can alter endometrial cytokine production, damage endometrial function [73], result in the formation of abnormal patterns of lymphocyte subsets in the EM, and induce the altered secretion of paracrine factors, which ultimately may reduce the receptivity of embryos in the EM [6066]. In fact, delayed differentiation of the EM in the mid-secretory phase (out-of-phase morphology) was observed in cases of CE [74].…”
Section: Pathophysiology Of Cementioning
confidence: 99%